2022
DOI: 10.1002/clc.23779
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial viability assessment and utility in contemporary management of ischemic cardiomyopathy

Abstract: Background: In clinical practice, we encounter ischemic cardiomyopathy (ICM) with underlying viable, dysfunctional myocardium on a regular basis. Evidence from the Surgical Treatment for Ischemic Heart failure (STICH) and its Extension Study is supportive of improved outcomes with coronary revascularization, irrespective of myocardial viable status. However, Dobutamine stress echocardiography (DSE) and single-photon emission computed tomography (SPECT), used in STICH to assess myocardial viability may fail to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Some researchers believe that the results of the STICH trial may be influenced by using SPECT and DSE which have suboptimal image resolution and could not distinguish between hibernating and scarred myocardium. They believe measuring myocardial viability with PET and CMR could precisely determine metabolically active myocardium and quantify myocardial scars [61].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers believe that the results of the STICH trial may be influenced by using SPECT and DSE which have suboptimal image resolution and could not distinguish between hibernating and scarred myocardium. They believe measuring myocardial viability with PET and CMR could precisely determine metabolically active myocardium and quantify myocardial scars [61].…”
Section: Discussionmentioning
confidence: 99%
“…Stunning is referred to the myocardium that is transiently ischemic and displays contractile dysfunction, which ultimately recovers early after restoration of normal resting blood flow. In the context of hibernating myocardium resting blood flow is severely reduced, while cardiac tissue remains viable by adaptively reducing contractility and cellular activity to decrease basal metabolic requests [ 35 ]. In contrast to stunned myocardium, hibernating myocardium usually recovers late after revascularization [ 36 ].…”
Section: Pathophysiologic Benefits Of Revascularizationmentioning
confidence: 99%
“…Prolonged myocardial hibernation may progress to necrosis, limiting functional recovery after revascularization. Extent of viability is also important, and several studies have shown that at least 25% to 30% of dysfunctional myocardium needs to be viable for improvement in LVEF after revascularization, with the except of extensively remodeled and dilated ventricles which could not recover after revascularization even in the presence of viable areas [ 34 , 35 , 36 ].…”
Section: Pathophysiologic Benefits Of Revascularizationmentioning
confidence: 99%
“…This then results in improved left ventricle ejection fraction (LVEF), clinical symptoms, long-term survival, and the effect of revascularization can be fully utilized. However, for the patients without viable myocardium, CABG provides little improvement [ 5 , 6 ], resulting in high risk of death [ 7 ]. In addition, surgeries could lead to trauma and complications, and possibly worsen the patient’s condition.…”
Section: Introductionmentioning
confidence: 99%